Attitudes and Practices that Shape Children's Drawing Behaviour in Mainstream and Performing Arts Schools. (February 2015) - Burkitt, Esther; Lowry, Ruth
Abstract Previous research shows that key parties involved in children's drawing perceive the value and benefits of art and drawing very differently. However such research has been restricted to the examination of children attending mainstream schooling across the UK. The present study therefore compared the views and practices of key parties involved in mainstream and performing arts educational contexts. Teachers and children were interviewed and parents completed a postal survey. Some 225 children, 115 of their teachers and 176 of their parents and carers formed the mainstream school group whilst 180 children, 42 of their teachers and 145 of their parents and carers formed the performing arts school group. Main findings indicated that pupils', parents' and teachers' views about the benefits, and how to support drawing behaviour at school and at home, varied across contrasting educational contexts. In particular, pupils attending arts‐based schools and their teachers valued expressivity over technical support, pupils reported enjoying drawing more, had higher self efficacy and foresaw engaging in the activity beyond their school years more than their mainstream counterparts. The results suggest that mainstream educational contexts could foster drawing behaviour and the related emotional benefits to a greater extent.